Bayesian geostatistical analysis and prediction of Rhodesian human African trypanosomiasis - Wardrop, N.A.; Atkinson, P.M.; Gething, P.W.; Fèvre, Eric M.; Picozzi, K.; Kakembo, A.S. (Public Library of Science, 2010)
The persistent spread of Rhodesian human African trypanosomiasis (HAT) in Uganda in recent years has increased concerns of a potential overlap with the Gambian form of the disease. Recent research has aimed to increase the evidence base for targeting control measures by focusing on the environmental and climatic factors that control the spatial distribution of the disease.